Status Quo Terrorism: State-Terrorism in South Africa during Apartheid - Taylor, Simon (Terrorism and political violence, 2023)
Defining state-terrorism is a contentious endeavor, with notably analytical impediments. Presented here is a definitive case of state-terrorism. As part of an effort to maintain the status quo of white hegemonic control, in 1979 the Apartheid state in South Africa created a police unit, known as Vlakplaas. Drawing from the Truth and Reconciliation Commission’s Final Report, clear evidence is presented demonstrating the Apartheid government’s use of Vlakplaas as an instrument of terrorism in order to instill terror in targeted audiences and to allay fears of the white electorate. As resistance to the status quo strengthened, so too did the terrorism methods used to maintain it. The methods used by Vlakplaas operatives included forms of violence that arguably ought to be considered state-terrorism—abductions, detentions, and torture—and methods traditionally associated with orthodox terrorism—bombings and killings.